Evaluation of newborn infants with caesarean section deliv-ery in Dr. Sardjito Central General Hospital - Sonny Issoedibyo, Sonny Issoedibyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
Two hundred and sixteen (9.1% of all deliveries) newborn infants with caesarean section in Dr. Sardjito Hospital during the period of November 1, 1982 to October 31, 1985 have been studied. It was shown that 54.4% of the cases with mothers age ranging between 25 Ã¢â¬â34 years, 40.5% of the mothers were primigravida and 67.6% with term gestational age. Caesarean section indications were placenta previa (47.7%), prolonged labour (23.0%) and cephalopelvic disproportion (16.4%) There were 76.4% of infants with a birth weight 2500 gram, 54.6% suffered from severe asphyxia and early neonatal deaths occurred in seven infants (3.2%). There were no significant differences between the type of caesarean section indications and the grade of asphyxia (p>0.05). A statistically significant difference was found between cases in 1 and 5 minute Apgar score resulted from resuscitation applied. There was also a highly significant difference between the grade of asphyxia and birth weight group (p